elisegayezm

2022-09-07

Asymptotes of a rational function
We have a function
$f\left(x\right)=\frac{2{x}^{4}+4{x}^{3}+3{x}^{2}+4x-4}{{x}^{3}-{x}^{2}-6x}$
How would I systematically go about finding the asymptotes of this function? I know how to find the asymptotes of for example log functions or functions with a square root in it, but I don't really know how to find them for this function.

Jase Powell

The problem can be simplified by dividing the numerator and denominator by (x+2):
$\frac{2{x}^{3}+3x-2}{{x}^{2}-3x}\phantom{\rule{0ex}{0ex}}$
Vertical asymptotes occur where y tends to infinity, which happens at the roots of the denominator:
${x}^{2}-3x=x\left(x-3\right)=0\phantom{\rule{0ex}{0ex}}$
There are two roots so the vertical asymptotes are x=0 and x=3.
Horizontal asymptotes occur where x tends to infinity, which becomes clear by dividing the numerator and the denominator by the highest power of x:
$\underset{x\to \mathrm{\infty }}{lim}\frac{2{x}^{3}+3x-2}{{x}^{2}-3x}=\underset{x\to \mathrm{\infty }}{lim}\frac{2+3/{x}^{2}-2/{x}^{3}}{1/x-3/{x}^{2}}=\mathrm{\infty }\phantom{\rule{0ex}{0ex}}$
There is no limit so there are no horizontal asymptotes.
Oblique asymptotes occur where the graph approaches the line (mx+b), which becomes clear by dividing the numerator and denominator:

There is a whole part so the oblique asymptote is y=2x+6.

Do you have a similar question?